FACTORS AFFECTING LOCALS’ ATTITUDES TOWARDS TAX ALLOCATION IN THE TOURISM SPHERE (IN THE CASE OF UZBEKISTAN) - Bahodirhon SAFAROV; Akhmadjon TANIEV; Bekzot JANZAKOV; Samariddin ALIQULOV; Jakhongir BAKHRAMOV (Geo Journal of Tourism and Geosites)
This article aims to analyze locals’ attitudes toward tax allocation in the tourism sphere in the Republic of Uzbekistan. The analysis is based on the survey data taken from 505 respondents. We explored the impact of the frequency of travelling, age, the importance of travelling, and total family income on people’s attitudes toward public financing of tourism using the ordinal logistic regression. The results show that increasing the frequency of travelling of each respondent increases the odds of people’s approval of financing tourism from taxes by two times. At the same time, surprisingly, the increase in family income reduces the probability of approving tourism’s budget financing. In brief, the research contributes to the stateof-the-art literature by analyzing factors affecting people’s opinions on tourism financing from tax inflow, which might play a crucial role in the development of tourism development strategies.